2017
DOI: 10.1088/1361-6463/aa85c4
|View full text |Cite
|
Sign up to set email alerts
|

Collective acceleration of ions in picosecond pinched electron beams

Abstract: Сharacteristics of intense electron-ion beams emitted by a high-voltage (280 kV) electron accelerator with a pulse duration of 200 ps and current 5 kA are studied. The capture phenomena and the subsequent collective acceleration of multi charged ions of the cathode material by the electric field of the electron beam are observed. It is shown that the electronion beam diameter does not exceed 30 µm therein in the case of lighter ions, and the decay of the pinched beam occurs at a shorter distance from the catho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 21 publications
0
1
0
1
Order By: Relevance
“…Previously, the authors in [4] showed that the imprint on the anode foil of a particle beam emitted by a high-voltage picosecond vacuum discharge with an extreme high energy input rate > 5×10 13 A/s has the form of concentric rings 2-5 mm in diameter. In this work, further studies of this effect were carried out in order to elucidate the possible mechanism for the formation of such structures.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, the authors in [4] showed that the imprint on the anode foil of a particle beam emitted by a high-voltage picosecond vacuum discharge with an extreme high energy input rate > 5×10 13 A/s has the form of concentric rings 2-5 mm in diameter. In this work, further studies of this effect were carried out in order to elucidate the possible mechanism for the formation of such structures.…”
Section: Introductionmentioning
confidence: 99%
“…Стимулом проведения таких исследований является общенаучный интерес к двум проблемам: необходимости изучения поведения конденсированных сред при высоких плотностях энергии и получению новых данных о физической природе таких явлений, как филаментация и самофокусировка электронных пучков в диодах со взрывоэмиссионным катодом, механизмы формирования которых окончательно не установлены. Отсутствие последовательной теории явлений филаментации и самофокусировки электронных пучков в вакуумных и газовых диодах сильноточных электронных ускорителей с различными параметрами стимулировало проведение экспериментальных работ, основанных на различных модельных представлениях [1,4,[6][7][8][9][10][11].…”
unclassified